The Effectiveness of Collaborative Learning to Enhance English Communicative Competence: A Case Study of the First-Year Students at Thepsatri Rajabhat University - Sasilak Rodphotong (International Journal of Pedagogy and Teacher Education, 2018)
The attempts of the present study aimed at investigating the effectiveness of collaborative learning to enhance English communicative competence and evaluating students’ satisfaction towards the instruction. The participants in this study were 1,471 the first-year students enrolled in the first semester, 2017 academic year. The students’ English proficiency according to the CEFR was A1. The instruments used were lesson plans, pre-test and post-test and satisfaction questionnaire. The lessons were comprised of various collaborative learning activities emphasizing at the following topics: self-introduction, school schedule, telling time, asking and giving information, food, leisure, describing people, describing things and giving direction. The period of experiment was 20 hours. The independent sample t-test was calculated to find the differences. The findings revealed that there were statistically significant differences at the level of .01 after teaching with collaborative learning. This indicated that the students’ communicative competence significantly improved. Besides, the satisfaction questionnaire was distributed at the end of the instruction and the results indicated that the students had a positive satisfaction towards the instruction.